Next generation sequencing technologies - Veeramah, Krishna (Henry Stewart Talks, 2009)
Sanger sequencing, The Archon Genomics Xprize, Sequencing by synthesis 454 sequencing by Roche, Solexa sequencing by Illumina, SOLid sequencing by ABI, Stats for the 3 main competitors, Some other methods, True single molecule sequencing, Sequencing by hybridization, Nanopore sequencing, Real time polymerase sequencing